The End of All Things. Morality and Terror in the Analysis of Kantian Sense of Sublime - Giulia Venturelli (Governare la paura, 2013)
The essay explores the philosophical concept of disaster within the Kantian ethical and religious thought. Kant’s notion of a «perverse end of all things» can in fact be seen as a focal point in the entire ethical and moral philosopher reflection, through the link placed in several of his writings between «morality» and «terror». The philosophical meaning of this relationship emerges in all its importance in the analysis of the feeling of the sublime, here analyzed in some Kant’s works, from the pre-critical Observations on the Feeling of Beautiful and Sublime, to his Critique of Judgment, Critique of Practical Reason and The End of All Things, in order to show how this reflection is undergoing a marked revaluation both in the contemporary philosophical debate and in performing arts.